Electrostatic steering enables flow-activated von Willebrand Factor to bind platelet glycoprotein, revealed by single-molecule stretching and imaging - Jiang, Yan (J Mol Biol, 2019)
Von Willebrand factor (VWF), a large multimeric blood protein, senses changes in shear stress during bleeding and responds by binding platelets to plug ruptures in the vessel wall. Molecular mechanisms underlying this dynamic process are difficult to uncover using standard approaches due to the challenge of applying mechanical forces while monitoring structure and activity. By combining single-molecule fluorescence imaging with high-pressure, rapidly-switching microfluidics, we reveal the key role of electrostatic steering in accelerating the binding between flow-activated VWF and GPIbα, and in rapidly immobilizing platelets under flow. We measure the elongation and tension-dependent activation of individual VWF multimers under a range of ionic strengths and pH levels, and find that the association rate is enhanced by four orders of magnitude by electrostatic steering. Under supraphysiologic salt concentrations, strong electrostatic screening dramatically decreases platelet binding to VWF in flow, revealing the critical role of electrostatic attraction in VWF-platelet binding during bleeding.